The Youth Fitness International Test (Yfit) Battery for Monitoring and Surveillance Among Children and Adolescents: A Modified Delphi Consensus Project with 169 Experts from 50 Countries and Territories - De Moraes-Ferrari, G (Elsevier B.V., 2025)
Background: Physical fitness in childhood and adolescence is associated with a variety of health outcomes and is a powerful marker of current and future health. However, inconsistencies in tests and protocols limit international monitoring and surveillance. The objective of the study was to seek international consensus on a proposed, evidence-informed, Youth Fitness International Test (YFIT) battery and protocols for health monitoring and surveillance in children and adolescents aged 6–18 years. Methods: We conducted an international modified Delphi study to evaluate the level of agreement with a proposed, evidence-based, YFIT of core health-related fitness tests and protocols to be used worldwide in 6- to 18-year-olds. This proposal was based on previous European and North American projects that systematically reviewed the existing evidence to identify the most valid, reliable, health-related, safe, and feasible fitness tests to be used in children and adolescents aged 6–18 years. We designed a single-panel modified Delphi study and invited 216 experts from all around the world to answer this Delphi survey, of whom one-third are from low-to-middle income countries and one-third are women. Four experts were involved in the piloting of the survey and did not participate in the main Delphi study to avoid bias. We pre-defined an agreement of ≥80% among the expert participants to achieve consensus. Results: We obtained a high response rate (78%) with a total of 169 fitness experts from 50 countries and territories, including 63 women and 61 experts from low- or middle-income countries/territories. Consensus (>85% agreement) was achieved for all proposed tests and protocols, supporting the YFIT battery, which includes weight and height (to compute body mass index as a proxy of body size/composition), the 20-m shuttle run (cardiorespiratory fitness), handgrip strength, and standing long jump (muscular fitness). Conclusion: This study contributes to standardizing fitness tests and protocols used for research, monitoring, and surveillance across the world, which will allow for future data pooling and the development of international and regional sex- and age-specific reference values, health-related cut-points, and a global picture of fitness among children and adolescents. © 2025